La santé environnementale : un autre regard sur le risque ou comment le savoir profane s’invite dans l’évaluation du risque - Valentine Erné-Heintz (Amnis)
Regarding chronic exposures, time durably blurs the causal link and plays against the victims. There is often a lag period between exposure and the appearance of the first symptoms. Victims rely on the discovery of a cluster and take the risk assessment by creating a community of interests. This lay knowledge from local knowledge alongside official expertise disrupts the risk analysis process. But more than an opposition, it is a circulation between several methodologies because the objective is not to substitute for scientific expertise but to raise a risk not taken into account or neglected by the public authorities.